Kepemimpinan yang Menebus di Sekolah Lentera Harapan Curug [Redemptive Leadership at Sekolah Lentera Harapan Curug] - Janwar J Juriaman; Dylmoon Hidayat (Universitas Pelita Harapan, 2017)
The Lentera Harapan Christian School in Curug has a vision and mission to proclaim the preeminence of Christ and to be actively involved in the redemptive restoration of all things through Him using holistic education. In leadership, the school has implemented redemptive leadership that is in line with the vision and mission of the school. The purpose of this research was to determine the understanding of the school's leaders of redemptive leadership characteristics. The study used a grounded theory of qualitative research. The instruments were interviews, documents, and open ended questionares. The data was collected from ten leaders and analyzed by open coding, axial coding, and selective coding. The research revealed four characteristics of redemptive leadership at the school: leadership that develops sin awareness, Christ-centered leadership, leadership that glorifies God, and leadership aimed at discipleship.BAHASA INDONESIA ABSTRAK:Sekolah Kristen Lentera Harapan Curug memiliki visi dan misi untuk menyatakan keutamaan Kristus dan terlibat aktif dalam pemulihan yang bersifat menebus segala sesuatu di dalam Dia melalui pendidikan Holistis. Dalam hal kepemimpinan, sekolah ini menerapkan kepemimpinan yang menebus yang sejalan dengan visi dan misi sekolah. Tujuan dari penelitian ini adalah untuk mengetahui pemahaman leaders mengenai gambaran kepemimpinan yang menebus. Penelitian ini menggunakan grounded theory yang merupakan bagian dari penelitian kualitatif. Data diperoleh dari hasil wawancara sepuluh leaders dan diolah dengan analisis koding terbuka, koding aksial, dan koding selektif. Hasil penelitian menngungkap 4 gambaran mengenai kepemimpinan yang menebus dalam penerapannya di sekolah tersebut yaitu kepemimpinan yang menyadarkan keberdosaan, kepemimpinan yang berpusat pada Kristus, kepemimpinan yang memuliakan Tuhan, dan kepemimpinan yang bertujuan untuk pemuridan.